1994
DOI: 10.1182/blood.v84.9.3122.3122
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in 998 unselected childhood acute lymphoblastic leukemia patients. Results and conclusions of the multicenter trial ALL-BFM 86

Abstract: In trial ALL-BFM 86, the largest multicenter trial of the Berlin- Frankfurt-Munster (BFM) study group for childhood acute lymphoblastic leukemia (ALL), treatment response was used as an overriding stratification factor for the first time. In the previous trial ALL-BFM 83, the in vivo response to initial prednisone treatment was evaluated prospectively. A blast cell count of > or = 1,000/microL peripheral blood after a 7-day exposure to prednisone and one intrathecal dose of methotrexate (MTX) identified 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
146
0
9

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 540 publications
(162 citation statements)
references
References 32 publications
7
146
0
9
Order By: Relevance
“…Many research protocols have defined induction failure as the presence of persistent leukemia after two cycles (or 2 months) of induction therapy 1, 2, 5, 6. Our data suggest that a more conservative definition of induction failure should be used.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Many research protocols have defined induction failure as the presence of persistent leukemia after two cycles (or 2 months) of induction therapy 1, 2, 5, 6. Our data suggest that a more conservative definition of induction failure should be used.…”
Section: Discussionmentioning
confidence: 80%
“…Ochs and colleagues19 reported that 12 of 27 (44%) patients achieved CR after one or two cycles with teniposide and cytosine arabinoside. The Berlin‐Frankfurt‐Munster (BFM) group2 reported that 9 of 20 (45%) children who were refractory to the first month of induction therapy achieved CR after treatment with cyclophosphamide, cytosine arabinoside, and 6‐mercaptopurine. In a study that included both adults and children, Giona and colleagues20 found that 7 of 13 (54%) patients who received idarubicin, cytosine arabinoside, and prednisone achieved CR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunophenotyping revealed a B‐II‐ALL positive for CD19, CD10, CD22, TdT and HLA‐DR. Treatment was performed according to the ALL‐BFM 86 protocol (Reiter et al , 1994) and the patient achieved remisson after 40 d, but relapsed 2 years and 3 months after diagnosis. At relapse biopsy of the testis showed infiltration with ALL blast cells and in the BM 45% of lymphoblasts were detected.…”
Section: Methodsmentioning
confidence: 99%